ANALISIS PENGALAMAN PENGGUNA DALAM MENGGUNAKAN TEKNOLOGI VIRTUAL REALITY PADA GAME CREED RISE TO GLORY DI GAMEBLINK PADANG - Dina Rudiva Agista; Zulfigo, Nella, Yoza, Melani, Hikmahtul Heneva, Dani dan Rini Novita (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
This study aims to analyze the user experience in using Virtual Reality (VR) technology in the Creed Rise to Glory game. The research method used is direct observation of a number of participants who play the game using VR devices. The results of the analysis show that users feel a sensation close to reality when interacting with the virtual environment in the game. In addition, users also reported a high level of engagement while playing the Creed Rise to Glory game with VR. This study shows that Virtual Reality technology is very effective in improving the user experience in playing the Creed Rise to Glory game. The use of VR technology can increase awareness and skills in playing games, as well as increase user satisfaction. However, it should be noted that some users have difficulty using VR technology. Therefore, it is necessary to improve and develop VR technology to improve user skills and satisfaction